A Comprehensive Strategy to Evaluate Compatible Stability of Chinese Medicine Injection and Infusion Solutions Based on Chemical Analysis and Bioactivity Assay - Li, Jian-Ping; Liu, Yang; Guo, Jian-Ming; Shang, Er-Xin; Zhu, Zhen-Hua; Zhu, Kevin Y.; Tang, Yu-Ping; Zhao, Bu-Chang; Tang, Zhi-Shu; Duan, Jin-Ao (Frontiers in Pharmacology, 2017)
Stability of traditional Chinese medicine injection (TCMI) is an important issue related with its clinical application. TCMI is composed of multi-components, therefore, when evaluating TCMI stability, several marker compounds can not represent global components or biological activities of TCMI. Till now, when evaluating TCMI stability, method involving the global components or biological activities has not been reported. In this paper, we established a comprehensive strategy composed of three different methods to evaluate the chemical and biological stability of a typical TCMI, Danhong injection (DHI). UHPLC-TQ/MS was used to analyze the stability of marker compounds (SaA, SaB, RA, DSS, PA, CA and SG) in DHI, UHPLC-QTOF/MS was used to analyze the stability of global components (MW 80-1000 Da) in DHI, and cell based antioxidant capability assay was used to evaluate the bioactivity of DHI. We applied this strategy to assess the compatible stability of DHI and six infusion solutions (GS, NS, GNS, FI, XI and DGI), which were commonly used in combination with DHI in clinic. GS was the best infusion solution for DHI, and DGI was the worst one based on marker compounds analysis. Based on global components analysis, XI and DGI were the worst infusion solutions for DHI. And based on bioactivity assay, GS was the best infusion solution for DHI, and XI was the worst one. In conclusion, as evaluated by the established comprehensive strategy, GS was the best infusion solution, however, XI and DGI were the worst infusion solutions for DHI. In the compatibility of DHI and XI or DGI, salvianolic acids in DHI would be degraded, resulting in the reduction of original composition and generation of new components, and leading to the changes of biological activities. This is the essence of instability compatibility of DHI and some infusion solutions. Our study provided references for choosing the reasonable infusion solutions for DHI, which could contribute the improvement of safety and efficacy of DHI. Moreover, the established strategy may be applied for the compatible stability evaluation of other TCMIs.